Diaphragm thickness is associated with overall survival in elderly thoracic trauma patients: - Tekin, Zeynep Nilufer; Bilgi , Zeynep (Vojnosanitetski pregled, 2025)
Background/Aim. Diaphragm thickness (DT) has been associated with advanced age and adverse outcomes, especially in severe conditions such as prolonged intubation. The aim of this study was to assess the prognosis of elderly patients with thoracic trauma (TT) and to investigate DT and psoas muscle thickness as potential prognostic indicators. Methods. A retrospective study included TT related consultations, taken from hospital records, performed between November 2015 and January 2021. Demographic data, injury characteristics, trauma mechanisms, overall survival, etc., were documented. Radiological imaging was re-evaluated to measure DT and psoas muscle thickness. Results. Among 394 patients, 129 were classified as elderly (> 65 years old). The most common mechanism of trauma was falls (n = 71), followed by pedestrian traffic accidents (n = 16). The overall survival of all patients was 43.9 ± 3.6 months, with an 82% two-year survival rate for elderly patients. DT was significantly higher in elderly survivors compared to deceased patients (4.0 ± 1.19 mm vs. 3.57 ± 1.0 mm; p = 0.015). Conclusion. Decreased DT is associated with an increased mortality risk in the elderly population. Elderly patients with TT and reduced DT may benefit from screening programs for early intervention targeting potential contributing factors such as frailty, trauma recidivism, and missed cancer screening. Furthermore, DT may serve as a potential indicator within a scoring system for risk assessment.